2018
DOI: 10.21475/ajcs.18.12.04.pne822
|View full text |Cite
|
Sign up to set email alerts
|

Applying plant oils to control fall armyworm (Spodoptera frugiperda) in corn

Abstract: Corn (Zea mays) is one of the world's main agricultural crops, and Spodoptera frugiperda (J. E. Smith) is its most important pest. In order to find natural controlling alternatives, this study aimed to determine the effect of plant oils on the feeding preference of first-and second-instar caterpillars. The experimental design was completely randomized in a 6 x 5 factorial combination (turmeric, clove, palmarosa, tea tree, common juniper, and neem oils) at five concentrations (0, 25, 50, 100, and 200 µL mL-1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Franco et al [74] demonstrated 100% FAW larval mortality with water extracts of seed of Carica papaya at 10% concentration. Plant oils from turmeric, clove, palmarosa and neem were shown to have significant positive effects of protecting maize from first and second instar FAW larvae [75].…”
Section: Use Of Locally Available Substances Toxic To Fawmentioning
confidence: 99%
“…Franco et al [74] demonstrated 100% FAW larval mortality with water extracts of seed of Carica papaya at 10% concentration. Plant oils from turmeric, clove, palmarosa and neem were shown to have significant positive effects of protecting maize from first and second instar FAW larvae [75].…”
Section: Use Of Locally Available Substances Toxic To Fawmentioning
confidence: 99%
“…A significant mortality of larvae of FAW has been reported from the use of aqueous seed extract obtained from Carica papaya which is similar to the mortality caused by Malathion (Figueroa-Brito et al, 2013). Similarly, the plant oils obtained from the turmeric, clove, palmarosa and neem have significant effects in controlling first and second instar of FAW larvae (Barbosa et al, 2018). Jirnmci, (2013) and Schmutterer (1985) reported that various botanicals extracts obtained from plants such as Azadirachta indica, Millettia ferruginea, Croton macrostachyus, Phytolacca docendra, Jatropha curcas, Nicotiana tabacum and Chrysanthemum cinerariifolium have been successfully used to control the FAW.…”
Section: Botanical Methodsmentioning
confidence: 99%
“…The upper part of the cage was sealed with voile fabric held by elastic gums. The cages were placed on light green plastic trays (adapted from Barbosa et al 2018). After the emergence of the adults, 50 mL plastic cups with a cotton swab soaked in an aqueous solution of honey were introduced into the PVC cages as food for the adults, and this process was used to obtain the adults and their oviposition.…”
Section: Methodsmentioning
confidence: 99%